Regulation and Implementation of Digital Broadcasting Monitoring in the Context of Freedom of Opinion in Indonesia - Saogi, Ahmad (Siyasah Dusturiyah: State Law Review, 2025)
This research analyses the gaps in digital broadcasting regulations in Indonesia in the context of protecting freedom of expression. Digital transformation, with internet penetration reaching 78.19% in 2023 and a projected digital economy worth 109 billion US dollars in 2025, has created new regulatory challenges, while the legal framework still relies on Law no. 32/2002, which was formed before the digital era. Through a juridical-normative approach and comparative analysis of regulatory practices in other countries, the research identified three critical findings: (1) the inability of the Broadcasting Law to accommodate the complexity of digital platforms due to the ambiguous definition of "other media"; (2) overlapping authority between KPI and Kominfo which results in legal uncertainty; and (3) a 52% increase in cases of criminalization of digital expressions related to politics in 2024, which indicates a systematic pattern of limiting criticism. The research recommends adopting a co-regulation model involving government, industry, and civil society; revising the ITE Law by removing the rubber article; and strengthening the Press Council as an independent mediator in digital journalistic content disputes. Harmonising broadcasting regulations with the principles of digital constitutionalism is the key to balancing the interests of state supervision and protecting citizens' constitutional rights.